2006
DOI: 10.4049/jimmunol.176.9.5374
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring CD4+Foxp3+ Regulatory T Cells Are an Essential, IL-10-Independent Part of the Immunoregulatory Network inSchistosoma mansoniEgg-Induced Inflammation

Abstract: In acute and chronic schistosomiasis, survival of the host requires a carefully balanced immune response against highly immunogenic parasite eggs. We characterized the phenotype, distribution, and functional role of CD4+Foxp3+ naturally occurring regulatory T cells (naTregs) in schistosome egg-induced inflammation. In adoptive transfer experiments and by intracellular staining for Foxp3, we demonstrate significant frequencies of naTregs in hepatic granulomas and draining lymphoid tissues of mice infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
125
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 67 publications
17
125
1
1
Order By: Relevance
“…These data are in line with a study demonstrating a more pronounced Th2 response in mice infected with the intestinal nematode Trichinella spiralis after removal of Treg by treatment with anti-CD25 Ab [19]. Studies using anti-CD25 Ab during filarial and schistosome infections also report on increased cytokine responses [15,16,18,24,31]. On the contrary, it has been shown recently that anti-CD25 Ab treatment during acute T. gondii infection impairs effector T-cell responses [26].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These data are in line with a study demonstrating a more pronounced Th2 response in mice infected with the intestinal nematode Trichinella spiralis after removal of Treg by treatment with anti-CD25 Ab [19]. Studies using anti-CD25 Ab during filarial and schistosome infections also report on increased cytokine responses [15,16,18,24,31]. On the contrary, it has been shown recently that anti-CD25 Ab treatment during acute T. gondii infection impairs effector T-cell responses [26].…”
Section: Discussionsupporting
confidence: 88%
“…We and others have shown that Treg produce IL-10 in a parasite-specific manner and thereby contribute to the antiinflammatory cytokine response seen as a hallmark of nematode infections [21,31,32]. However, studies with Schistosoma mansoni-infected mice clearly showed that effector T cells are the dominant source of IL-10 during infection [18,[31][32][33]. Our current study suggests that non-Treg are the dominant source of IL-10 during intestinal nematode infections.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations